Screening of biodegradation potential for n-alkanes and polycyclic aromatic hydrocarbon among isolates from the north-western tip of Pahang - Sharif, Mohd Faez; Azizan, Nur Hafizah (2020)
This study has successfully screened for a few selected enzyme activities and hydrocarbon-degrading capability of 18 bacterial isolates from the north-western tip of Pahang. The bacterial isolates were known belong to genus Pseudomonas, Stenotrophomonas, Acinetobacter, Serratia, Bacillus and Exiguobacterium. Among them there are more than 80% were lactase and amylase producers, while only 44% were protease and lipase producers. Gravimetric analysis was performed to test the capability of degrading n-alkanes and polycyclic aromatic hydrocarbons (PAHs). A statistical analysis, Statistical Package for the Social Sciences (SPSS) was used for hydrocarbon utilization analysis. The overall degradation of n-alkanes was revealed to be not significant. On the other hand, based on the statistical analysis PAHs utilization was significant. Isolate A3i was chosen as the best utilize of n-alkanes, while isolate A2 was chosen for the best PAHs degrader.